KEAMANAN DATABASE MENGGUNAKAN METODE ENKRIPSI - Suyanto, Suyanto (Universitas Bina Darma, 2012)
Growing data processing technology, this has resulted in the implementation of computerized systems in all fields. All parts of the organization or company has implemented various applications to meet their needs. Applications are applied separately raises its own problems which need the same data. So that data exchange becomes an alternative solution. Data security requirements on the database exchange process are become new problems in the process. To ensure data security on the exchange process, the encryption method is the best way. With the implementation of encryption on data that is exchanged, then the data is guaranteed safe and can only be read by those who need it. Applications that use different databases require a standard format so that all applications can read it. This format is XML. With XML, the database (tables) can be read by other applications though with different platforms. Keywords:Encryption, Decryption, Security, Database, Cipher, XML.